Magnetic triggers in biomedical applications – prospects for contact free cell sensing and guidance. Issue 5 (7th January 2021) - Almeida, Ana F.; Vinhas, Adriana; Gonçalves, Ana I.; Miranda, Margarida S.; Rodrigues, Márcia T.; Gomes, Manuela E.
Abstract : This review overviews the unique cues of magnetic nanoparticles as sophisticated and resourceful nanotools for advanced diagnosis and therapy-oriented technologies. Abstract : In recent years, the inputs from magnetically assisted strategies have been contributing to the development of more sensitive screening methods and precise means of diagnosis to overcome existing and emerging treatment challenges. The features of magnetic materials enabling in vivo traceability, specific targeting and space- and time-controlled delivery of nanomedicines have highlighted the resourcefulness of the magnetic toolbox for biomedical applications and theranostic strategies. The breakthroughs in magnetically assisted technologies for contact-free control of cell and tissue fate opens new perspectives to improve healing and instruct regeneration reaching a wide range of diseases and disorders. In this review, the contribution of magnetic nanoparticles (MNPs) will be explored as sophisticated and versatile nanotriggers, evidencing their unique cues to probe and control cell function. As cells detect and engage external magnetic features, these approaches will be overviewed considering molecular engineering and cell programming perspectives as well as cell and tissue targeting modalities. The therapeutic relevance of MNPs will be also emphasized as key components of nanostructured systems to control the release of nanomedicines and in the context of new therapy technologies.